Prevention of Space Charge Accumulation and Space Charge Induced Breakdown Using Electrets - Saha, Pradip Chandra; Faruqe, Omar; Park, Chanyeop (Electrical Insulation Conference and Electrical Manufacturing Expo, 2023)
In this study, we numerically and experimentally demonstrate the validity of incorporating electrets for space charge induced dielectric breakdown prevention. Numerical models that represent our experiments have been built and simulated in COMSOL Multiphysics software. The simulation results clearly exhibit the prevention of space charge injection and accumulation that can be achieved via electrets. In the experimental validation, first, we fabricate electrets using the polyvinylidene fluoride (PVDF) by triode corona charging and measure the charge embedded in the electrets through an electrostatic voltmeter. Second, we measure the breakdown voltage of a regular dielectric and a regular dielectric coated with an electret film under DC voltage. The difference in the breakdown voltage of the two cases will demonstrate the efficacy of electrets as the prevention mechanism of space charge injection and accumulation.